Predictors of neuropsychological late effects and white matter correlates in children treated for a brain tumor without radiation therapy. Issue 10 (16th July 2019) - Peterson, Rachel K.; Tabori, Uri; Bouffet, Eric; Laughlin, Suzanne; Liu, Fang; Scantlebury, Nadia; Mabbott, Donald
Abstract: Background: Little is known about cognition and predictors of neuropsychological outcomes in pediatric low‐grade glioma (PLGG) survivors treated without radiation therapy. This research expands upon our previous work by further identifying the cognitive profile of PLGG patients treated without radiation therapy, investigating the specific medical and demographic variables that predict functioning, and examining white matter structure and its relationship to neuropsychological performance. Procedure: Nineteen PLGG patients (11‐19 years) were administered the Wechsler Intelligence Scale for Children/Wechsler Adult Intelligence Scale, and subtests from the Woodcock‐Johnson Tests of Cognition (visual matching, rapid picture naming, and pair cancellation) and Cambridge Neuropsychological Test Automated Battery (pattern recognition memory, delayed matching to sample, intra‐extra dimensional set shift, motor screening task, rapid visual information processing, and spatial span). Results: The sample had normative weaknesses in verbal working memory, brief attention/vigilance, psychomotor speeded output, visual perception and matching, overall cognition, working memory, and processing speed. Increased surgeries or subtotal resections, hydrocephalus, shunting procedures, chemotherapy, NF1, and supratentorial location were predictive of cognitive deficits. Broad white matter involvement of the frontal, temporal, parietal, and occipital lobes as well as the cerebellum, as inferred from diffusion tensor imaging indices of decreased fiber orientation and increased water diffusion, was related to many cognitive difficulties. Conclusions: This study comprehensively examines cognitive functioning in PLGG patients treated without radiation therapy, predictors of cognition, and its relation to white matter structure. Our findings indicate that medical and demographic variables other than radiation therapy can lead to cognitive late effects with diffuse white matter involvement.